The Effect of Training and Commitment on the Performance of Village Business Entity (BUMDes) Management in Kampar Regency Riau Province - Ali Hamzah; Susi Hendriani; Kurniawaty Fitri (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
This study aims to see the effect of training and commitment on the performance of BUMDes management in Kampar Regency, Riau Province. The samples of this study were 30 BUMDes from 5 Districts in Kampar Regency. Questionnaires were distributed to 30 respondents, and successfully collected with complete answers from 30 respondents. Primary data were collected through a questionnaire as the instrument to prove the results of the study. Multiple linear regression analysis with the help of the SPSS program were used to test the hypothesis of the study. Data collected from 30 respondents then were analyzed with the assistance of SPSS software version 23.0 using descriptive statistical analysis and multiple linear regression analysis to generate a classical assumption test, data analysis model, coefficient of determination and proving the hypothesis. The results of the study show that: 1) there is positive and partially significant effect of training on the performance of BUMDes management in Kampar District, 2) there is positive and significant effect of partial commitment on the performance of BUMDes management in Kampar Regency, 3) there is a simultaneous positive and significant influence of training and commitment on the performance of the managers of BUMDes management in Kampar Regency.